A modified nonparametric univariate Control chart for location based on the trimmed mean - Moustafa, O; Abu-Shawiesh,; Mokhtar Abdullah, (Universiti Kebangsaan Malaysia, 2001)
This paper develops a modified approach to the computation of control limits and central line for the Hodges-Lehmann control chart proposed by Alloway & Raghavachari (1991). The modified approach is based on replacing the median of the Walsh averages by the a-trimmed mean, in the Hodges-Lehmann estimator. A numerical example is given to illustrate the use of the modified approach. It is performance is compared with that of Alloway & Raghavachari (1991) using some simulation studies.